Investigation of the relationship between personality characteristics and vasomotor symptoms in menopausal women - Mahboubeh Ghorbani; Sedigheh Azhari; Habib Allah Esmaily; Bahram Ali GhanbariHashemabadi (Wolters Kluwer Medknow Publications, 2016)
Background: Research demonstrates that most of the menopausal symptoms and problems are the reflection of individual and social circumstances rather than the endocrine events of the menopause. As majority of women live 30 years or more through postmenopausal period, treatment and following up their problems during this period is among the main duties of a midwife. The aim of this study is to determine the relationship between personality traits and vasomotor symptoms in postmenopausal women. Materials and Methods: This correlation study was conducted on 400 postmenopausal women referring to the training maternity centers of Mashhad, Iran. Subjects were selected through simple sampling method and filled NEO Five-Factor Inventory (NEO-FFI (questionnaire. Their daily records of hot flashes and night sweats were also collected. NEO-FFI questionnaire assesses the five personality aspects of neuroticism, extraversion, openness to experience, conscientiousness, and agreeableness. After the data were collected, they were analyzed by Pearson and Spearman correlation coefficients, Mann-Whitney, Kruskal-Wallis, and linear regression statistical tests. P < 0.05 was considered as a statistically significant value. Results: Most of the women were in average level of personality traits. Among the aspects of personality traits, there was a significant correlation between intensity of hot flashes (P = 0.041) and night sweats (P = 0.028), and conscientiousness. Conclusions: According to the results of the study, during treatment of the vasomotor symptoms, a midwife should pay close attention to the personality of postmenopausal women to achieve an effective treatment. These women should also be referred to a psychologist, if needed.